2021
DOI: 10.1021/acs.jpcb.0c09406
|View full text |Cite
|
Sign up to set email alerts
|

Defect-Induced Double-Stranded DNA Unwinding on Graphene

Abstract: Several works have shown that graphene materials can effectively regulate the double-stranded DNA (dsDNA) structures and are used to remove antibiotic resistance genes in the environment, during which the morphology of the graphene surface plays a key role. However, the mechanism of how different graphene surfaces interact with dsDNA is poorly documented. Here, the interactions of dsDNA with defective graphene (D-Gra) and pristine graphene (P-Gra) have been explored by molecular dynamics simulations. Our data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…In this study, we chose the time scale of 1 µs to ensure that the potential interaction behaviors that may occur on longer time scales could be captured and we could avoid the omission of any important interaction behaviors, which is consistent with the published article. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we chose the time scale of 1 µs to ensure that the potential interaction behaviors that may occur on longer time scales could be captured and we could avoid the omission of any important interaction behaviors, which is consistent with the published article. [ 15 ]…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we chose the time scale of 1 μs to ensure that the potential interaction behaviors that may occur on longer time scales could be captured and we could avoid the omission of any important interaction behaviors, which is consistent with the published article. [15] Using aromatic ring-functionalized molecules was the most widely reported method to mediate the binding of probe NA to the graphene surface in G-FET NA detection. [16] These molecules typically consisted of one or more aromatic and reactive functionalized groups.…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous experience in studying the interaction of DNA with carbon nanotubes, e.g., in ref , we decided to set the simulation times to 45 ns. In scientific literature, papers on similar topics can be found in which authors conducted simulations for much longer times, e.g., 100 ns or even 1000 ns but we think that in our case it is possible to simulate a little shorter. This is confirmed by the values of parameters monitored during the simulation, e.g., the root of mean squared displacement (RMSD) of the i-motif from its initial state.…”
Section: Calculation Methodsmentioning
confidence: 92%
“…Similarly, Li et al studied the adsorption of a dsDNA on defective graphene sheets. 81 Defects on graphene were modeled as a vacancy in the structure, comprising 12 carbon atoms saturated by alternative hydroxyl groups and hydrogen atoms (Figure 5(f)). They observed that the dsDNA adsorption on defective graphene started via the adsorption of the terminal base pairs on a pristine section, followed by interaction with the defective section through H-bonding and electrostatic interactions.…”
Section: Double-stranded Dna (Dsdna)mentioning
confidence: 99%